Preliminary Study of a New Topology Permanent Magnet Flux Switching Motor for Electric Buses - M. F. Omar; E. Sulaiman; M. Z. Ahmad; J. A. Rani; Aravind CV (Institute of Advanced Engineering and Science, 2018)
Electric buses (EBs) as public transit that have been introduced in modern countries recently are an alternative effort to reduce climate change and environmental impacts of fossil fuels. One example of the successfully developed motor for EBs is interior permanent magnet synchronous motor (IPMSM) with merits of heat dissipating, high torque per frame size and reliability influence by absence of brushes. However, the three-phase armature windings are wounded in the form of distributed windings, results in much copper loss, high coil end length and reduced the efficiency. The embedded rectangular magnets inside the rotor make rotor less robust, increased rotor weight and reduced the torque and power density. The present IPMSM has a complex structure which is relatively difficult to manufacture and tough in optimization process. The 7.0 kg volume of PM used in IPMSM is very high, which increases the cost of the machine. Therefore, a new topology of permanent magnet flux switching motor using wedge-shaped PM and single stator structure with the advantages of simple stator design, robust rotor structure, high of torque and power, and high efficiency is proposed. The design, flux linkage, back-emf, cogging torque, average torque, speed, and power of this new topology are investigated by JMAG-Designer version 14.1 via a 2D-FEA. The initial design of proposed motor produces torque and power of 905.9 Nm and 57.75 kW, respectively.